A TUTELA DA INTEGRIDADE DO PROCESSO ELEITORAL CONTRA A DESINFORMAÇÃO: ENTRE A RETÓRICA ELEITORAL LÍCITA E A DESINFORMAÇÃO ILÍCITA - Leite, Alaor; Borges, Ademar (Revista da AJURIS - Qualis A2, 2022)
PROTECTING THE INTEGRITY OF THE ELECTORAL PROCESS AGAINST DISINFORMATION: BETWEEN LEGAL ELECTORAL RHETORIC AND ILLICIT DISINFORMATION SUMÁRIO: A. A consulta; B. Direito material: a retórica eleitoral permitida e a desinformação ilícita; C. Direito processual: dinamismo processual e a tutela judicial efetiva da integridade do processo eleitoral; D. Resposta aos quesitos. SUMMARY: A. The consultation; B. Substantive law: permitted electoral rhetoric and illicit disinformation; C. Procedural law: procedural dynamism and effective judicial protection of the integrity of the electoral process; D. Answer to the questions.